Relationship of the Number of Black Dots in the Nuclei of Argyrophilic Nucleolar Organizing Regions (AgNORs) Expressed Epithelial Cells with Nottingham Grading System in Invasive Breast Carcinoma of No Special Type (IBC-NST) - Mohd. Yuwanda Basrul; Delyuzar Delyuzar; T. Kemala Intan; Soekimin Soekimin; T. Ibnu Alferraly (Majalah Patologi Indonesia, 2026)
Background Breast cancer is a malignant disease in women. The high number of breast cancer cases is caused by multiple factors, including barriers to early detection of breast cancer, socio-economic and geographical factors, and the difficulty of affordable, timely and effective health services. IBC-NST has the highest incidence among breast cancer cases with a 10 year survival rate (65-78%). AgNORs parameters have been shown to represent a reliable tool for determining the clinical outcome of cancer diseases, being an independent prognostic factor in many types of tumors.   Method Descriptive analytics research was carried out on slides from 31 patients with IBC-NST. Each slide was stained with H&E stainning to assess the Nottingham grading system and stained with AgNORs to assess the number of black dots in epithelial cell nuclei that expressed AgNORs. All clinicopathological data were taken from medical records/pathology archives. Logistic regression test (p<0.005) was used to assess the relationship between the number of black dots in epithelial cell nuclei expressing AgNORs and the Nottingham grading system in IBC-NST.   Results The highest cases were in the age group ≤40-50 years (range: 50.1 years), the highest grading was in grade 3 of the Nottingham grading system (48.8%), the lowest number of black dots was 576 dots and the highest was 1,036 dots (mean 798.80, median 710.0 and standard deviation 144.71) and the highest number of black dots was in grade 3 of the Nottingham grading system.   Conclusion Assessment of the number of black dots in the nuclei of epithelial cells expressing AgNORs associated with Nottingham grading system can be used as an indication of prognosis in patients with IBC-NST.